Inovasi Metode Pembelajaran Al- Qur’an - Masykur, Abdul Rosyid; Ritonga, Rafika Sulami; Najamuddin , Najwa (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
Innovation in the method of learning the Qur'an is important to increase the effectiveness and attractiveness of the learning process, especially in facing the challenges of the digital era. This study aims to explore various forms of innovation in the method of learning the Qur'an that have been applied in various Islamic educational institutions. The approach used is a qualitative study with data collection techniques through observation, interviews, and documentation. The results of the study show that innovations such as the use of digital media, thematic approaches, interactive tilawah methods, and gamification can increase students' motivation and understanding of the contents of the Qur'an. In addition, the involvement of creative teachers and the use of technology are the main keys to successful learning. These findings indicate that innovation in the method of learning the Qur'an is very relevant and necessary to create a Qur'anic generation that is adaptive to the development of the times.